S90 Homocystine levels in non-small cell lung cancer. (16th November 2010) - Maguire, J; Kelly, V; Smyth, C; Ledson, M; Walshaw, M
Abstract : Plasma homocystine level is the most sensitive marker of sub-clinical folate deficiency. Elevated levels of homocystine have been associated with several pathologies, particularly vascular and cardiac disease. Patients with lung cancer are frequently elderly and may have insufficient intake of folate. Sub-clinical folate deficiency may lead to increased morbidity during chemotherapy and radiotherapy, and possibly reduced response rates to both treatment modalities. We have measured plasma homocystine levels in 460 patients with a diagnosis of non-small cell lung cancer who were referred to our lung cancer unit between 2005 and 2009. Two hundred and fifty-six patients were male, 204 were female. The median age was 71. 22% of patients were PS 0-1, 35% PS2 and 43% PS3. The local laboratory reference range for homocystine is ≤15 μmol/l. 43% of patients had elevated plasma levels of homocystine at diagnosis. In 35% the level was between 15.1 and 25 μmol/l, and in 8% the homocystine level was greater than 25 μmol/l. Patients with elevated plasma homocystine levels had inferior median and 1 year survival rates, both for stage III disease (464 vs 356 days ms, 1 year survival 65% vs 47%) and stage IV disease (212 vs 190 days ms, 1 year 30% vs 21%). The finding of elevated homcystine levels in 43% of newly diagnosed patients with non-small cell lung cancer is of potentially profound significance, as this implies that there could be a possible therapeutic benefit from folate and B12 supplementation before and during treatment for this group of patients with non- small cell lung cancer.